Using Digital Fairy Tale Book in Teaching Reading Comprehension - kurniati, utut (Universitas Swadaya Gunung Jati, 2018)
ABSTRACT The researcher aims to investigate whether the Digital Fairy Tale Book effective in teaching reading comprehension. Theories used to support this research are from Patel and Jain (2008) about the audio visual media and reading. Audio visual media involves more than one sensory organs of the learner which improves retentiveness and makes learning permanent also seeing and hearing go together which play ordinary roles in learning. Meanwhile, reading is very important for the teacher to carry out, to know, and to check the students’ pronunciation, information, stress, paused, and rhythm and their ability in various short of punctuation marks. The researchers used experimental research of method, and took two classes consisting of 30 students each class as sample in SMP Al Washliyah Sumber. The data for this experimental study were students’ reading scores, and the reading scores were analyzed of using McMillan and Schumacher’s formula. The research found that the reading scores of the experimental group is higher than the control group. The result of t account is 0.75, t table is 1,672 for α = 5% it means that t account is higher than t table (t account > t table). Therefore, the conclusion is Digital Fairy Tale Book is effective in teaching reading comprehension. It makes the students enthusiastic to learn the fairy tale text and help them produce correct intonation or tunes and notice how English is spoken differently from the way they are written and listen very well. It is suggested to use of Digital Fairy Tale Book in Teaching Reading as an alternative media in order to students’ ability in Reading Aloud other genres of texts or to improve students’ listening skill. Keywords : Digital Fairy Tale Talking Book, Reading Aloud, Fairy Tale Text